Myxoinflammatory fibroblastic sarcoma of the thigh: A morphologic diversity - Vanisri H Raghavan (Thieme Medical and Scientific Publishers Pvt. Ltd., 2012)
Myxoinflammatory fibroblastic sarcoma (MIFS)/acralmyxoinflammatory fibroblastic sarcoma (AMFS) is a rare, painless, low-grade neoplasm which commonly occurs in the extremities. It has a distinctive morphology and can be a diagnostic challenge, simulating inflammatory conditions as well as neoplastic conditions. They are low-grade sarcomas with a protracted clinical course, a high rate of local recurrence and a low rate of metastasis. We report a case of proximal MIFS in a 50-year-old woman who presented with a mass in the thigh.